Singapore income taxation - OOI, Vincent (Institutional Knowledge at Singapore Management University, 2018)
28.1.1 Section 10(1) of the Income Tax Act (Cap. 134, 2014 Rev. Ed.) (“ITA”) is the charging provision which provides for income tax to be payable for each year of assessment (“YA”) upon the income of any person. Income is taxable if it falls within one of the enumerated heads of charge under sections 10(1)(a) to (g).Income is taxable only if it is sourced in Singapore, i.e. accruing in or derived from Singapore, or received in Singapore from outside Singapore, subject to variations.Only revenue (and not capital) receipts are taxable, and only revenue (and not capital) expenses are deductible for the purpose of computing the taxable income of a person.